2020
DOI: 10.1007/s41252-020-00157-8
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Changes in Urinary Metabolites and Behaviors with the Use of Leucovorin Calcium in Children with Autism Spectrum Disorder (ASD)

Abstract: Objectives Children with autism spectrum disorder (ASD) have been found to have a high prevalence of folate receptor autoantibodies (FRAA), which may impair the normal transport of folate from blood into the cerebrospinal fluid (CSF). Leucovorin calcium (LC) is believed to bypass the folate transport system and restore function. We sought to examine changes in behavior and urinary metabolites in children and young adults with ASD being treated with LC. Methods Students attending a K-12 school for ASD were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…As seen in Figure 1, 20 studies were identified which studied d,l-leucovorin treatment in individuals with ASD including four placebo-controlled studies [72][73][74][75], three prospective, controlled studies [37,44,76], nine prospective studies without a control group [20,21,[33][34][35][77][78][79][80] (two studies examined the same cohort of patients [78,79]), and four case reports/series [36,[67][68][69].…”
Section: Treatment Of Asd With Dl-leucovorinmentioning
confidence: 99%
See 3 more Smart Citations
“…As seen in Figure 1, 20 studies were identified which studied d,l-leucovorin treatment in individuals with ASD including four placebo-controlled studies [72][73][74][75], three prospective, controlled studies [37,44,76], nine prospective studies without a control group [20,21,[33][34][35][77][78][79][80] (two studies examined the same cohort of patients [78,79]), and four case reports/series [36,[67][68][69].…”
Section: Treatment Of Asd With Dl-leucovorinmentioning
confidence: 99%
“…Supplementary Table S6 lists the five studies [37,72,74,80,81] performed by three different sets of investigators which have examined the use of d,l-leucovorin in children with idiopathic ASD without additional treatments in order to determine if d,l-leucovorin administered by itself is a useful treatment for ASD. Table 4 outlines the effect sizes of some of the key outcome measures used in these studies.…”
Section: Treatment With Dl-leucovorin In General Asd: Leucovorin Onlymentioning
confidence: 99%
See 2 more Smart Citations